Wireless biometric information exchange system - Casaque, Rafael R.; Castro, Joao Luiz de; Benini, Fabriciu A. V. (Seven Editora, 2023)
This work is part of the seventh scientific initiation of the project called SEAID (Embedded System for Fingerprint Acquisition). This edition resulted in the physical and practical implementation of the knowledge generated in previous works. Initially, wireless communication was implemented between two Raspberry Pi devices using socket architecture, with one device acting as a client and the other as a server, to establish a connection and enable the exchange of images captured by the biometric modules. Additionally, the Fast Fourier Transform (FFT) algorithm was integrated into both devices. This algorithm was used to measure the frequency similarity between two different images, aiming to achieve greater accuracy in evaluating them as belonging to the same individual’s fingerprint. With these modifications, the main objective is to use one device as a fingerprint collector, creating a repository for storage, and another device as a validator, making requests to the images stored in the first device to test the developed algorithm. It compares the current fingerprint with each previously saved image, verifying if there is a match. DOI:https://doi.org/10.56238/alookdevelopv1-192